FAMILY AND SCHOOL CONDITION TOWARD STUDENT ENGLISH ACHIEVEMENT - Syahrilla putri, Verdana islami Alwi; Syahrul, Syahrul; Melani, M. (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
The school environment is also an inhibiting factor for students. For example, the way the lesson is presented is not good. In addition, there are still many parents who ignore the education of their students. This has an impact on students' low English skills. This study aims to analyze family and school conditions on students' English achievement. This research is a correlational study. The research subjects were all students of the class with 24 students. The method used to collect data is observation, interviews, and questionnaires. The instrument used in data collection is a questionnaire. The technique used to analyze the data is descriptive qualitative statistics, and quantitative. The study results are that family conditions have a positive effect on learning achievement in learning English. This shows that when family conditions improve, student achievement will also increase. Partial test (t-test) obtained t count variable influence of family conditions = 6.607 so that Ha X1 against Y is accepted. Variable influence of school conditions t count = 3.019 so that Ha X2 to Y is accepted. The practical contribution of family conditions is 21.316%, school conditions are 39.678%. The key is that there is a simultaneous influence of family and school conditions on learning English subjects.